Reproductive Biology Study of Silver Barb Barbonymus gonionotus (Bleeker: 1849) in the Waters of Way Sekampung Dam, Pagelaran District, Pringsewu Regency, Lampung - Ilham Hadi Prasetyo; Rara Diantari; Rizha Bery Putriani (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
Barbonymus gonionotus silver barb, is one type of consumer fish that has great potential to be developed. Silver barb have an important role in maintained the balance of aquatic ecosystems. In order to maintained the sustainability of silver barb resources in Way Sekampung Dam, it is necessary to analyzed the biological aspects of silver barb. This researched was conducted in September-December 2024 at Way Sekampung Dam, Pagelaran District, Pringsewu Regency, Lampung. The purpose of this study is to analyzed the biological aspects of silver barb reproduction which includes sex ratio, gonad maturity stages (GMS), gonad somatic index (GSI), fecundity, egg diameter and analyzed the type of silver barb spawning. Fish samples were obtained from one of the local fishermen who caught fish using gill nets. The sex ratio of silver barb obtained shows that male silver barb are more than female silver barb, during the study male fish amounted to 250 fish while females amounted to 167 fish. Most of the silver barb obtained are fish that have not matured gonads, namely in phases I to III, GMS IV and V are most commonly found in November and December. Based on the calculation of GSI, the percent value of GSI obtained is 0.035-13.858% for male fish and 0.155-14.269% for female fish. The fecundity of silver barb obtained an average of 47,192 eggs. The diameter of silver barb eggs was calculated and the results ranged from 0.27-0.85 mm. The results of measuring egg diameter also show a graph that has one peak, which means that silver barb in Way Sekampung dam have a total spawner type.